An Analysis of Cirebon City Regional Regulation Number 4 of 2013 on the Prohibition of the Distribution and Sale of Alcoholic Beverages in Cirebon City - Fihri Musthofa; Fawwaz Musthofa (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2025)
This study aims to provide a comprehensive analysis of Cirebon City Regional Regulation Number 4 of 2013 concerning the Prohibition of the Distribution and Sale of Alcoholic Beverages. The primary focus of this research lies in examining the substance of the regulation, particularly the formulation of the definition of “alcoholic beverages,” as well as its implementation through public dissemination and law enforcement mechanisms. The study employs a qualitative approach using content analysis of regulatory documents, supported by relevant literature review. The findings indicate that there is potential ambiguity in the definition of “alcoholic beverages” as stipulated in the regulation, which may lead to multiple interpretations among law enforcement authorities and the public. This ambiguity poses challenges to the effective implementation of the policy, particularly in monitoring and enforcement processes. Furthermore, the study reveals that dissemination efforts have not been fully optimal in terms of coverage and intensity, resulting in varying levels of public understanding regarding the regulation. In addition, law enforcement faces several constraints, including limited resources and inconsistencies in the application of sanctions. Based on these findings, the study concludes that the successful implementation of the regional regulation largely depends on the clarity of its normative substance, the effectiveness of dissemination strategies, and the consistency and firmness of law enforcement. Therefore, it is necessary to refine the definition to be more precise and operational, enhance public outreach efforts, and strengthen coordination among law enforcement agencies to achieve the intended regulatory objectives effectively.